Impacts of reducing water collection times in rural Kenya: Meru ESM RCT - Impacts of reducing water collection times in rural Kenya: School-aged Children - Kabubo-Mariara, Jane; Kimuyu, Peter; Cook, Joseph (University of Gothenburg, 2022)
We measured momentary well-being using the Experience Sampling Method (ESM) among 220 water collectors in rural Meru County, Kenya over eight weeks. Subjects reported on affect and time use at four randomly-chosen times through the day (Monday through Saturday) on a custom-designed ODK survey app, deployed on a low-cost smartphone. Subjects completed a second ODK survey each weekday evening, reporting on school attendance, study time and chores performed for each school-aged child in the household. After several weeks of baseline data, half of households were randomly chosen to receive free delivery of water to their door for four weeks, reducing water collection times to (near) zero. In-person baseline, midline and endline surveys were conducted by enumerators.

The data from the daily survey of school-children is in the file “Meru schoolkids.dta”. These can be linked back to the household level data in “Meru ESM RCT” using phoneid, and to the child-specific variables using the variable “pid”. The matching was done based on manually matching names in the baseline survey and this schoolchildren survey. To protect confidentiality, these names cannot be included. Where the pid field is missing either the name of the child was missing or could not be reasonably matched to the name of a child in the household.

We measured momentary well-being using the Experience Sampling Method (ESM) among 220 water collectors in rural Meru County, Kenya over eight weeks. Subjects reported on affect and time use at four randomly-chosen times through the day (Monday through Saturday) on a custom-designed ODK survey app, deployed on a low-cost smartphone. Subjects completed a second ODK survey each weekday evening, reporting on school attendance, study time and chores performed for each school-aged child in the household. After several weeks of baseline data, half of households were randomly chosen to receive free delivery of water to their door for four weeks, reducing water collection times to (near) zero. In-person baseline, midline and endline surveys were conducted by enumerators.

The data from the daily survey of school-children is in the file “Meru schoolkids.dta”. These can be linked back to the household level data in “Meru ESM RCT” using phoneid, and to the child-specific variables using the variable “pid”. The matching was done based on manually matching names in the baseline survey and this schoolchildren survey. To protect confidentiality, these names cannot be included. Where the pid field is missing either the name of the child was missing or could not be reasonably matched to the name of a child in the household.
Impacts of reducing water collection times in rural Kenya: Meru ESM RCT - Impacts of reducing water collection times in rural Kenya: School-aged Children
Keywords: rural areas; landsbygd; water collection; vattentäkt; experience sampling method; erfarenhetsinsamling; time use; tidsanvändning; ECONOMICS; EKONOMI; Economic systems and development; Ekonomiska system och ekonomisk utveckling; Social conditions and indicators; Sociala förhållanden och indikatorer; Time use; Tidsanvändning; PSYCHOLOGY; PSYKOLOGI; Social Sciences; Samhällsvetenskap